2017
DOI: 10.1042/bcj20160998
|View full text |Cite
|
Sign up to set email alerts
|

The CD9, CD81, and CD151 EC2 domains bind to the classical RGD-binding site of integrin αvβ3

Abstract: Tetraspanins play important roles in normal (e.g. cell adhesion, motility, activation, and proliferation) and pathological conditions (e.g. metastasis and viral infection). Tetraspanins interact with integrins and regulate integrin functions, but the specifics of tetraspanin-integrin interactions are unclear. Using co-immunoprecipitation with integrins as a sole method to detect interaction between integrins and full-length tetraspanins, it has been proposed that the variable region (helices D and E) of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…CD151 can also interact with other tetraspanin family members (e.g. CD9, CD81) and integrins to regulate migration, adhesion and signaling of cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD151 can also interact with other tetraspanin family members (e.g. CD9, CD81) and integrins to regulate migration, adhesion and signaling of cells [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confinement effects play an important role in different physical phenomena especially in quantum systems like Bose-Einstein condensates, superconductors, and superfluids. For example, the ability to structure superconducting devices at length scales comparable to the characteristic sizes (penetration dept λ and coherence length ξ ) of the condensate revealed a vast world of possibilities to explore quantum phenomena (e.g., creation of artificial atoms [1], induction of quantum phase slip lines [2], confinement effects [3], to name a few). In the latter example, theoretical modeling of these systems solving the Ginzburg-Landau (G-L) [4,5] or Bogoliubov-deGennes (B-dG) [6] equations for single and/or multiband mesoscopic superconductors has been done.…”
mentioning
confidence: 99%
“…Interestingly, Jeong et al demonstrated synergistic activities of GPR56 and α3β1 integrin during cerebral cortical development (34), which may account for GPR56 activation of integrin partners such as Src-Fak. Additionally, GPR56-interacting proteins including CD81 and collagen III (24,35) have also been shown to associate with integrins (36)(37)(38). The STP region overlaps with the PLL domain which shares sequence similarity to LNS domains which can mediate cell adhesion (19,39).…”
Section: Discussionmentioning
confidence: 99%